Modelling inflation-interest rate nexus for Ghana - Yeboah, Samuel Asuamah (International Journal of Financial, Accounting, and Management, 2020)
Purpose: The research assesses the interest rates-inflation association in the case of Ghana between 2007 and 2013. Monthly and quarterly data were used. Research Methodology: The model of the vector error correction and Johansen were used to investigate the long-term and short-term association in the model estimated respectively. The vector autoregression (VAR) test was used to model the joint dynamics between the variables. GRETL software was used in these tests. Granger predictive test was done with the EViews software. Results: The findings of the result confirm both long-run and a short-run association in the model and as well as neutral granger predictive causality. Limitations: Though the Johansen test is more appropriate for multivariate modelling, Engle-Granger test is considered to be more robust in most cases and as such future studies should consider using the two models in a comparative study to assess whether the current conclusions can collaborate. Contribution: The paper contributes to knowledge in the field of inflation and Interest rates association, in relation to the financial markets. Future Research models that account for structural breaks and panel works are worth doing. Keywords: Fisher effect, Treasury bill rates long run, Johansen model